A POLYMYOSITIS AFTER mRNA COVID-19 VACCINATION CASE REPORT - Özkara Yılmaz, Buket (MNJ (Malang Neurology Journal), 2024)
Polymyositis is a rare, acquired, and inflammatory muscular disease, which is characterized by the inflammation of muscles and has no known etiology. The autoimmunity created by the vaccine arose from molecular mimicking or directly by vaccine adjuvants. Polymyositis cases were reported after hepatitis B, influenza A (H1N1), tetanus toxoid, and Bacille Calmette-Guerin (BCG) vaccinations. However, no relationship with COVID-19 vaccination has been reported yet. Myositis and dermatomyositis cases have been seen after covid-19 vaccine. m-RNA COVID-19 vaccines might cause abnormal activation of the immune system due to a strong t-cell-mediated immune activation by vaccinesin the present case, without any additional triggering factor, a case diagnosed with polymyositis developing 10 days after the second dose of messenger RNA (mRNA) COVID-19 vaccine is presented. The findings suggest a potential association between mRNA COVID-19 vaccination and the development of polymyositis, prompting further investigation into this rare occurrence.